1983
DOI: 10.1210/jcem-56-6-1131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapy for Differentiated Carcinoma of the Thyroid: An Analysis of 706 Cases*

Abstract: A retrospective analysis of clinical and pathological data was conducted on 706 patients (514 females and 192 males) treated for differentiated thyroid carcinoma at The University of Texas M. D. Anderson Hospital and Tumor Institute at Houston from 1951 to 1975 and followed to 1981. The histological diagnoses were mixed papillary/follicular carcinoma (66.7%), papillary carcinoma (14.6%), follicular carcinoma (15.3%), or Hurthle cell carcinoma (3.4%). Patients diagnosed before the age of 40 yr lived significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
100
1
22

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(135 citation statements)
references
References 21 publications
12
100
1
22
Order By: Relevance
“…Russell, et al, 2 reported an incidence of 65% papillary and papillarypredominant and 35% follicular and follicular-predominant, based upon whole organ section. Samann, et al, 12 reported an incidence of papillary and mixed types of 81%, and follicular of 15%. Farrar, et al, 13 reported an incidence of 80% papillary and 20% follicular.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Russell, et al, 2 reported an incidence of 65% papillary and papillarypredominant and 35% follicular and follicular-predominant, based upon whole organ section. Samann, et al, 12 reported an incidence of papillary and mixed types of 81%, and follicular of 15%. Farrar, et al, 13 reported an incidence of 80% papillary and 20% follicular.…”
Section: Discussionmentioning
confidence: 99%
“…This could suggest a more favorable prognosis, since papillary type carries a better prognosis than follicular type. 2,3,12,14 Out of 78 differentiated carcinomas, there were 27 (35%) males and 51 (65%) females; a male:female ratio of 1:1.9. This is consistent with Cady's 3 findings of an increasing incidence of males with differentiated carcinoma in succeeding decades from 19% in the 1930's to 34% in the 1960's, with resulting changes in male:female ratio during the period from 1:4 to 1:2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DTC recurrence rate has been reported to be 1.4-23% (8,9) and depends on the initial and ongoing risk stratification (10). The mortality of patients with a recurrence has been shown to be as high as 38-69% (11,12). Furthermore, 2-5% of patients with initially differentiated tumors can develop refractoriness to radioiodine and iodine-131 ( 131 I)-negative metastases.…”
Section: Introductionmentioning
confidence: 99%